Molecular and Cellular Responses of DNA Methylation and Thioredoxin System to Heat Stress in Meat-Type Chickens - Habashy, Walid S. (Animals (Basel), 2021)
SIMPLE SUMMARY: Performance traits and mortality are negatively affected by heat stress. The responses of chickens to HS are extremely complex. Understanding of the molecular mechanism of DNA methylation and the TXN system under HS may provide a new strategy to mitigate the effect of HS. Based on our results, the thioredoxin pathway system under HS may provide clues to nutritional strategies to mitigate the effect of HS in meat-type chicken. ABSTRACT: Heat stress (HS) causes molecular dysfunction that adversely affects chicken performance and increases mortality. The responses of chickens to HS are extremely complex. Thus, the aim of this study was to evaluate the influence of acute and chronic exposure to HS on the expression of thioredoxin–peroxiredoxin system genes and DNA methylation in chickens. Chickens at 14 d of age were divided into two groups and reared under either constant normal temperature (25 °C) or high temperature (35 °C) in individual cages for 12 days. Five birds per group at one and 12 days post-HS were euthanized and livers were sampled for gene expression. The liver and Pectoralis major muscle were sampled for cellular analysis. mRNA expression of thioredoxin and peroxiredoxins (Prdx) 1, 3, and 4 in the liver were down-regulated at 12 days post-HS compared to controls. The liver activity of thioredoxin reductase (TXNRD) and levels of peroxiredoxin1 (Prdx1) at 12 days post-HS were significantly decreased. The results reveal that there was a significant decrease in DNA methylation at 12 days post HS in liver tissues. In conclusion, pathway of thioredoxin system under HS may provide clues to nutritional strategies to mitigate the effect of HS in meat-type chicken.